The Missing Link: Public Policy for the Private Sector in Central and East European Higher Education - Kwiek, Marek (My University, 2003)
In the last half a century, despite immense growth in enrollments, European public higher education remained relatively stable from a qualitative point of view and its fundamental structure remained unchanged. No major changes occurred that could be as revolutionary as changes we are currently witnessing. The forces of change worldwide are similar and they push higher education systems towards more market-oriented and more competitive arenas (and certainly towards less state regulation). For centuries, "the market" had no major influence on European higher education. Most (modern) universities were created by the state and subsidized by the state; most students attended public institutions and most faculty worked in public institutions. Today market forces are invading higher education: while the form and pace of change is different in different parts of the world, that change is happening everywhere. The growth of the private sector in European post-communist countries is part of a much larger picture in which the restructuring of the whole public sector, the retrenchment of the welfare state, increasing privatization and marketization of public services generally and the influence of the forces of globalization are most visible.
Keywords: Central Europe; Eastern Europe; private higher education; public policy; private sector; European integration; Bologna Process